Teachers’ Euphemism on Language Learning: Sociolinguistics Study in Higer Education - Amiruddin, Mohammad; Zuhri, Muhammad Darrin; S, Evha Nazalatus, (UIBU, 2025)
The goal of this research was to identify the teachers' euphemism language in language learning, as well as the roles of euphemism in supporting students' language learning. This was a qualitative research that used a descriptive case study approach. This qualitative descriptive study explored teachers’ use of euphemism in language learning and examined its role in supporting students’ learning motivation. This study's participants included students and teachers from Madura University. Data on euphemism and its effects on language development were gathered through observation and interviews. The results of the study showed that there were five euphemisms used by instructors in language learning: (1) outspoken, (2) large boned, (3) curvaceous, (4) distinctive, and (5) exceptional. 25 % of students claim that professors use